2011
DOI: 10.3382/ps.2011-01390
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent thermal manipulations of broiler embryos during late incubation and their immediate effect on the embryonic development and hatching process

Abstract: Intermittent high (+3°C) and low (-3°C) temperature treatments for 4 h on embryonic day (E) 16, E17, and E18 showed differential effects on embryonic metabolism, without influencing embryonic growth or hatchability. Embryos in the high-temperature group shifted to a more anaerobic metabolism, as indicated by a lower partial pressure of O(2) and a higher partial pressure of CO(2) in the air cell, lower blood pH, and higher lactic acid production. Three hours after the end of the high-temperature treatment, a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 18 publications
3
27
1
1
Order By: Relevance
“…With respect to cooler temperatures, Shinder et al (2009) reduced incubation temperature to 15℃ for 30 or 60 min at EA 18 and 19 and observed an increase in body weight at hatch without affecting hatchability. In contrast, Willemsen et al (2010Willemsen et al ( , 2011 reported that reducing incubation temperature by 3℃ at EA 16 to 18 did not influence either embryo growth or hatchability. It was also found that plasma T 3 which has an important role in the hatching process and thermoregulatory mechanisms (Decuypere et al, 1979;Debonne et al, 2008) was lowered at external pipping stage when eggs incubated at lower temperature (Willemsen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to cooler temperatures, Shinder et al (2009) reduced incubation temperature to 15℃ for 30 or 60 min at EA 18 and 19 and observed an increase in body weight at hatch without affecting hatchability. In contrast, Willemsen et al (2010Willemsen et al ( , 2011 reported that reducing incubation temperature by 3℃ at EA 16 to 18 did not influence either embryo growth or hatchability. It was also found that plasma T 3 which has an important role in the hatching process and thermoregulatory mechanisms (Decuypere et al, 1979;Debonne et al, 2008) was lowered at external pipping stage when eggs incubated at lower temperature (Willemsen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although current literature provides relevant information on the effects of variations of incubation temperature in broilers (Kidd, 2004;Yahav et al, 2004b;Yalçin et al, 2005;Piestun et al, 2008;Yalçin et al, 2008;Ghonim et al, 2009;Yahav, 2009;Leksrisompong et al, 2007;Willemsen et al, 2011, Druyan et al, 2012Selim et al, 2012, Loyau et al, 2013, few studies were carried out with layers (Salimet al,2005;Walstra et al, 2010). The present study aimed at evaluating the influence of high incubation temperature on the incubation and blood parameters, and organs weights of layer chicks.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental temperature is reported as the most critical physical factor affecting embryo development and hatchability (Yalçin & Siegel, 2003). Excessive heat inside incubator may reduce hatching efficiency (Willemsen et al,2011;Boleli & Queiroz, 2012) and yolk-free body mass (Lourens et al, 2007;Hulet et al, 2007;Leksrisompong et al, 2007), and may affectchick growth after hatching (Tona et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Incubation temperatures above that considered optimal for domestic poultry (37-38°C; Romanoff, 1960;French, 1997) negatively affect hatchability and reduce both hatchling quality (Hagger et al, 1986;French, 2000;Leksrisompong et al, 2007;Willemsen et al, 2011;Boleli & Queiroz, 2012) and growth performance after hatch (Decuypere et al, 1979;Geers et al, 1982).…”
Section: Introductionmentioning
confidence: 99%